Comparing the Effect of In2O3 and Eu2O3 Impurities on the Structural and Optical Properties of Cerium Oxide - Rasheed, Mustafa M.; Hasan, Bushra A. (Iraqi Journal of Science, 2024)
This work compares the changes in optical and structural properties of cerium oxide (CeO2) when doped with different concentrations (3%,5%,7%, and 9%) of two oxides, In2O3 and Eu2O3. X-ray diffraction and spectrophotometry were employed in the visible, ultraviolet, and near-infrared regions. The findings demonstrated that CeO2 doped with In2O3 and Eu2O3 thin films were polycrystalline and had a cubic structure. The crystal size increased from 20.5 to 32.15 when Eu2O3 doping ratio increased from 0% to 7% and then decreased to 28.46 nm at 9%. While the crystal size showed an increase from 20.5 to 21.42 nm with the increase of the In2O3 doping ratio, while the lattice constant measured for cubic CeO2 changed opposite to that. The optical measurement showed that Eu2O3 and In2O3 doped CeO2 thin films have a direct band gap with allowed transition with 3.0 eV for the undoped CeO2. The band gap energy changed in a non-regular manner with the increase of the doping ratio of both oxides. The minimum band gap energy was 1.2 eV obtained for 7% Eu2O3 doped CeO2 thin film, and the minimum band gap energy was 1.4 eV obtained for 9% In2O3 doped CeO2. These results qualify them for use as absorbers in solar cell applications.